Land use intensity determines soil properties and biomass recovery after abandonment of agricultural land in an Amazonian biodiversity hotspot - Cecilio Rebola, Loïc; Pandolfo Paz, Claudia [UNESP]; Valenzuela Gamarra, Luis; F.R.P. Burslem, David (Elsevier, 2021)
There has been widespread clearance of tropical forests for agriculture, but in many cases the cultivation phase is only transient. The secondary forests recovering on these abandoned sites may contribute to mitigation of greenhouse gas emissions and protection of biodiversity, but the rates of recovery may be dependent on land-use intensity and changes in soil properties during cultivation. However fine-scale details on these changes are poorly known for many tropical forest locations. We quantified soil properties and recovery of woody biomass in 42 tropical forest fragments representing a chronosequence following two types of agricultural land-uses, and in 15 comparable reference old growth forests, between the Andes and the Amazon in Peru. Soil fertility, particularly base cation concentrations, responded negatively to increasing intensity of agricultural land-use, and either decreased or increased with time after abandonment dependent on prior land-use. The predicted mean recovery rate of woody biomass over the first 20 years following abandonment matched that predicted by a general model for the Neotropics, but recovery was three-fold higher on sites abandoned following traditional agriculture than on sites recovering from intensive agriculture. Estimated total biomass recovered to just above half that of reference old growth forests within 71 years. The inclusion of the biomass of lianas and smaller tree stems did not modify the apparent rate of ecosystem biomass recovery, however the proportion of the total biomass stored in small stems was greater following intensive than traditional agriculture, which suggests that patterns of stand structural development are sensitive to land-use history. We conclude that effects of historic land use on soil nutrient concentrations and their changes through time are required for a more complete interpretation of variation in biomass recovery rates at local scales. These results also highlight the critical importance of contemporary agricultural intensification for carbon storage in tropical forests.
Keywords: Agricultural intensification; Biomass resilience; Land-use change; Peru; Soil fertility; Tropical forest